Science in the School Playground - Cavalheiro, A.; Calvo, E.; Santos, M. A.; Costa, V. (Open Schools Journal for Open Science, 2020)
How to improve our school playground? Based on the school plan and the surrounding area, it was decided to promote scientific activities in the playground by sharing scientific knowledge. In these activities, 20 pupils and 4 teachers participated as organizers, covering a community of 244 pupils (ages 3-10), 18 teachers and 11 other school staff. We chose a set of scientific questions, connected with the knowledge of space, the influence of the Sun in our lives, and with the protection of bats. We promote the questions through two tools: a conference and an exhibition, both organized by the students. The conferences were prepared in small groups, by exploring and using reliable scientific sources such as Ciência Viva science centres and ESERO Portugal. In the exhibition, scientific knowledge was offered at the school playground, in an experimental, interactive and dynamic approach, where we were the facilitators and guides of the other students and the educational community.